The application of the coacervation technique for microencapsulation bioactive ingredients: A critical review - Nezamdoost-Sani, Narmin; Amiri, Saber; Mousavi Khaneghah, Amin (Journal of agriculture and food research, 2024)
Microcapsules obtained from microencapsulation technology consist of an active inward kernel substance and an external layer or crust that protects and covers the kernel substance. Microencapsulation is applied in different disciplines, such as food and pharmaceutical. Coacervation, as a separator of colloidal composition into two liquid phases, is the second common method of capsulation in food industries. It provides high encapsulation efficiency and bioactive compounds-controlled liberation, may be influenced by temperature and physical and biological mechanisms, and offers desirable flexibility that patronages the development of extensive food. Bioactive ingredients include antioxidants, vitamins, peptides, multiple unsaturated fatty acids, phytosterols, lutein, lycopene, and probiotics. Their sensitivity usually restricts the application of bioactive components. Coacervation can create a protective obstacle and optimal diffusion and compatibility characteristics in different environments. In this review article, the research results in the range of 2015–2024 and the useful content of related articles related to the subject were collected from various databases such as ScienceDirect and google scholar. In general, the bioactive compounds encapsulated by the microencapsulation method, especially the complex coacervation method and their advantages, the wall and core materials used, microencapsulation conditions, and finally, the results of the research are collected attractively and comprehensively. Complex coacervation could be a promising, interesting, and useful method to protect and deliver substances, such as polyunsaturated fatty acids, vitamins, antioxidants, peptides, phytosterols, lutein, lycopene, pigments and phenolic acids, enzymes, essential oils, and probiotics, for controlled release applications during storage and delivery in the gastrointestinal tract. Considering the advantages of bioactive components, it seems necessary to pay attention to microencapsulation methods, especially occlusion, to solve limitations in this field and to optimize the conditions and parameters of the coacervation, especially the complex coacervation. [Display omitted] •Encapsulation of bioactive ingredients protects them from unwanted effects and controls their release.•Complex coacervates have been applied to enclose essential oils, carotenoids, anthocyanins, and vitamins.•The main advantages of coacervation encapsulation are high Encapsulation Efficiency (EE) (up to 99 %).